Graphite negative electrode and preparation method and application thereof

By adopting multi-component graphite negative electrode material, combining sphericalization and coating technology, the kinetics and energy density are balanced, the limitations of existing graphite negative electrode materials in specific capacity, compaction density, cycle performance and high-temperature performance are solved, and the limitations of existing graphite negative electrode materials are achieved. Highly efficient lithium-ion battery performance improvement.

CN119447177APending Publication Date: 2025-02-14ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2

Patent Information

Application Number
CN202411619167.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have shown limitations in specific capacity, compaction density, circulation performance, lithium extraction and capacity recovery rate after high-temperature storage, and are difficult to meet the needs of lithium-ion batteries in terms of energy density and cycle life.

Method used

Using multi-component graphite negative electrode material, including graphite component 1, graphite component with low cladding content 2, graphite component 3 of conductive cladding layer and single-particle structure Component 4: By adjusting the content and particle size of each component, the contradiction between kinetics and energy density is equalized.

Benefits of technology

The high specific capacity and high compaction density of graphite negative electrode materials are achieved, while improving circulation and high temperature performance, ensuring that the capacity recovery rate of the battery after high temperature storage reaches more than 89%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447177A_ABST
    Figure CN119447177A_ABST
Patent Text Reader

Abstract

The invention relates to the related technical field of secondary batteries, and discloses a graphite negative electrode and a preparation method and application thereof. The graphite negative electrode comprises an active substance, the active substance comprises at least two of a graphite component 1, a graphite component 2, a graphite component 3 and a graphite component 4, and the active substance does not only comprise the graphite component 1 and the graphite component 4 at the same time; each of the graphite component 1 and the graphite component 2 has a secondary particle structure, the graphite component 1 is a spheroidized secondary particle, and the graphite component 2 contains a coating layer; the graphite component 3 and the graphite component 4 both have single-particle structures, the graphite component 3 contains a coating layer, and the graphite component 4 does not contain a coating layer. The graphite negative electrode has high specific capacity and compaction density, further has good cycle performance, and can well solve the problems of lithium precipitation and capacity recovery rate after high-temperature storage (for example, the capacity recovery rate after 84 days of storage at 60 DEG C exceeds 89% and even exceeds 90%).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to secondary batteries, and in particular to a graphite negative electrode and a preparation method and application thereof. Background Art

[0002] Although traditional lithium-ion batteries have been widely used in the market, there are many challenges in further improving their energy density and power density. There are also some challenges in electrode material stability, electrolyte window limitations, and electrode structure design. Graphite, as the traditional choice of negative electrode material for lithium-ion batteries, has the advantages of high electronic conductivity, large lithium ion diffusion coefficient, stable layered structure, and low lithium insertion potential. It is one of the most widely used and technologically mature negative electrode materials in commercialization. However, with the continuous improvement of lithium-ion battery performance requirements, traditional graphite negative electrode materials have gradually shown limitations in performance such as specific capacity and compaction density, cycle performance, lithium precipitation, and capacity recovery rate after high-temperature storage (high-temperature performance).

[0003] Therefore, it is urgent to develop a high-capacity, high-density graphite negative electrode material that will significantly improve the energy density and cycle life of lithium-ion batteries, and provide more efficient and reliable energy solutions for electric vehicles, portable electronic devices, and large-scale energy storage systems. CN116190562A provides a negative electrode sheet and its preparation method and battery, which improves the fast charging capability while ensuring the high energy density of lithium-ion batteries through a double active material coating, a low-compacted upper layer, and a high-compacted lower layer structural design. However, this method has high processing costs and difficulties, and there are problems such as low initial efficiency, cycle diving, and poor high-temperature performance during the actual use of the battery cell.

[0004] The graphite negative electrode is the key factor limiting the rate of the battery cell. The existing technical solutions include: setting the graphite material layer, modifying the graphite material (surface coating, mixing amorphous carbon); setting the pole piece layer, reducing the pole piece thickness, and reducing the pole piece compaction density. However, the above modification of graphite often comes at the expense of capacity, increasing the difficulty of pole piece manufacturing, and shortening the cycle life. In addition, although reducing the thickness and compaction density of the pole piece shortens the lithium ion diffusion distance and increases the pole piece porosity, which is beneficial to reducing the charging polarization, the proportion of active materials is reduced, and the energy density is reduced accordingly. Under the condition that both energy density and fast charging are equally important, it is not worth adopting the method of sacrificing energy density in exchange for improving fast charging. In addition, the graphite negative electrode obtained by the existing method also has technical problems such as poor cycle performance, lithium precipitation, and capacity recovery rate (high temperature performance) after high-temperature storage.

[0005] Therefore, there is an urgent need to provide a new graphite negative electrode that can solve the problems of specific capacity, compaction density, cycle performance, lithium precipitation, and capacity recovery rate after high-temperature storage (high-temperature performance) without sacrificing energy density. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a graphite negative electrode and a preparation method and application thereof. The graphite negative electrode has a high specific capacity and compaction density, and further has good cycle performance, and can also well solve the problems of lithium deposition and capacity recovery rate (high temperature performance) after high temperature storage.

[0007] The invention also provides a graphite negative electrode.

[0008] The invention also provides a method for preparing the graphite negative electrode.

[0009] The invention also provides a graphite negative electrode sheet.

[0010] The invention also provides a method for preparing a graphite negative electrode sheet.

[0011] The present invention also proposes the application of the graphite negative electrode.

[0012] According to one aspect of the present invention, a graphite negative electrode is provided, comprising an active material, wherein the active material comprises at least two of a graphite component 1, a graphite component 2, a graphite component 3, and a graphite component 4, and does not comprise only the graphite component 1 and the graphite component 4 at the same time;

[0013] The graphite component 1 and the graphite component 2 both have a secondary particle structure, and the graphite component 1 is a secondary particle that has been spheroidized, and the graphite component 2 contains a coating layer;

[0014] The graphite component 3 and the graphite component 4 both have a single particle structure, and the graphite component 3 contains a coating layer, while the graphite component 4 does not contain a coating layer.

[0015] In some embodiments of the present invention, the graphite component 1 accounts for 0-30% of the mass of the active material; and / or, the graphite component 2 accounts for 0-70% of the mass of the active material; and / or, the graphite component 3 accounts for 0-70% of the mass of the active material; and / or, the graphite component 4 accounts for 0-30% of the mass of the active material; and / or, the particle size D of the graphite component 1 50 Between 11.5-14 μm; and / or, the particle size D of the graphite component 2 50 Between 13-15 μm; and / or, the particle size D of the graphite component 3 50 Between 9-13 μm; and / or, the particle size D of the graphite component 4 50 Between 8-11μm.

[0016] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: the graphite negative electrode of the present invention comprises an active material, the active material comprises at least two of four different graphite components, and the content and particle size D of each graphite component are 50 Due to specific selection, the graphite negative electrode of the present invention has high specific capacity and compaction density. Furthermore, it also has good cycle performance and can well solve the problems of lithium plating and capacity recovery rate after high-temperature storage (for example, the capacity recovery rate after storage at 60°C and 84 days exceeds 89%, or even exceeds 90%).

[0017] The graphite negative electrode of the present invention balances the contradictory relationship between the kinetics (cycle performance) and energy density of the graphite negative electrode by adjusting the dosage and particle size of each different graphite component in the active material, and balances the high temperature and kinetic performance by introducing the graphite component 1; the coating agent technology is used in the graphite component 2 to reduce the coating amount, which effectively improves the kinetic performance of the active material on the one hand, and ensures that the high temperature performance and cycle life of the active material are not deteriorated on the other hand; the graphite component 3 and the graphite component 4 of the single particle structure respectively improve the capacity and compaction density of the active material and reduce the cost, which is beneficial to ensure the high temperature performance, thereby achieving the characteristics of good kinetics of the battery under high capacity and high compaction.

[0018] The present invention designs a multi-component graphite negative electrode and utilizes the different advantages and characteristics of each graphite component to balance the dynamics and energy density of the negative electrode plate; the two secondary particle components, graphite component 1 and graphite component 2, can be regarded as dynamic performance switches, and the quantitative control of the fast charging performance can be achieved by adjusting their proportions; the two single particle components, graphite component 3 and graphite component 4, are used as the cornerstones of the capacity and compaction density of the graphite negative electrode to ensure the energy density and high temperature performance of the graphite negative electrode.

[0019] In some embodiments of the present invention, the particle sizes of the graphite component 1, the graphite component 2, the graphite component 3, and the graphite component 4 are different from each other, which is beneficial to reduce the voids in the active material and improve the compaction density.

[0020] In some embodiments of the present invention, the active material comprises graphite component 2, graphite component 3 and graphite component 4. The active material formed by combining the three graphite components has better cycle performance and high temperature performance than the active material formed by combining other two or three graphite components.

[0021] In some embodiments of the present invention, the coating layer in the graphite component 1 is composed of soft carbon. The raw material for preparing the soft carbon of the coating layer of the graphite component 1 is conventional asphalt.

[0022] In some embodiments of the present invention, the graphite component 1 accounts for 0-30% of the mass of the active material, further 10-25%, further 10-20%, specifically, for example, 10%, 15%, 20%, 25%.

[0023] In some embodiments of the present invention, the particle size D of the graphite component 1 is 50 The thickness is between 11.5 and 14 μm, further between 12 and 14 μm, and further between 12.5 and 13.5 μm. Specifically, for example, 12 μm, 12.5 μm, 13 μm, 13.5 μm, and 14 μm.

[0024] In some embodiments of the present invention, the graphite component 2 accounts for 0-70% of the mass of the active material, further 15-60%, further 40-60%, specifically, for example, 15%, 20%, 30%, 40%, 50%, 60%.

[0025] In some embodiments of the present invention, the particle size D of the graphite component 2 is 50 The thickness is between 13 and 15 μm, further between 13 and 14.5 μm, and further between 13.5 and 14.5 μm. Specifically, for example, it is 13 μm, 13.5 μm, 14 μm, and 14.5 μm.

[0026] In some embodiments of the present invention, the graphite component 3 accounts for 0-70% of the mass of the active material, further 10-60%, further 10-20%, specifically, for example, 10%, 20%, 30%, 40%, 50%, 60%.

[0027] In some embodiments of the present invention, the particle size D of the graphite component 3 is 50 The thickness is between 9 and 13 μm, further between 9.5 and 12.5 μm, and further between 10 and 12 μm. Specifically, for example, it is 9.5 μm, 10 μm, 11 μm, and 12 μm.

[0028] In some embodiments of the present invention, the graphite component 4 accounts for 0-30% of the mass of the active material, further 10-30%, further 10-20%, specifically, for example, 10%, 15%, 20%, 25%, 30%.

[0029] In some embodiments of the present invention, the particle size D of the graphite component 4 is 50 The thickness is between 8 and 11 μm, further between 9 and 11 μm, and further between 9.5 and 10.5 μm. Specifically, for example, it is 9 μm, 9.5 μm, 10 μm, and 10.5 μm.

[0030] In some embodiments of the present invention, both the graphite component 1 and the graphite component 2 contain a coating layer, and the mass proportion of the coating layer in the graphite component 1 is greater than the mass proportion of the coating layer in the graphite component 2.

[0031] In some embodiments of the present invention, the graphite component 1 contains a coating layer, which accounts for 1.2-2%, or further 1.5-2% of the mass of the graphite component 1. The mass proportion of the coating layer is also called the residual carbon value, that is, the residual carbon value is 1.2-2%.

[0032] In some embodiments of the present invention, the coating layer in the graphite component 2 accounts for 0.2-1.5% of the mass of the graphite component 2, and further 0.5-1%.

[0033] In some embodiments of the present invention, the coating layer in the graphite component 2 is composed of hard carbon, soft carbon, graphene, solid electrolyte or carbon nanotube.

[0034] The raw material for preparing the coating hard carbon of the graphite component 2 is at least one of cross-linked asphalt, resin, and biomass carbon source. Biomass carbon source includes corn straw, soybean straw, and wheat straw; resin includes polycarbonate resin and epoxy resin.

[0035] In some embodiments of the present invention, the coating layer of the graphite component 3 is a conductive coating layer.

[0036] In some embodiments of the present invention, the conductive coating layer of the graphite component 3 is composed of at least one selected from graphene, carbon nanofibers, and MXene (MXene is a two-dimensional material made of carbides or nitrides of transition metals).

[0037] According to another aspect of the present invention, a method for preparing the above-mentioned graphite negative electrode is provided, comprising the following steps:

[0038] The various graphite components are mixed to obtain the graphite negative electrode.

[0039] In some embodiments of the present invention, the raw material of the graphite component 1 includes petroleum coke, such as raw petroleum coke and calcined petroleum coke.

[0040] In some embodiments of the present invention, the mass percentage of sulfur in the petroleum coke is less than or equal to 1.5%. The relatively small impurity content helps to maintain the electrochemical performance of the graphite negative electrode.

[0041] In some embodiments of the present invention, the preparation process of the graphite component 1 includes: spheroidizing petroleum coke, graphitizing it, adding asphalt, and granulating it to obtain the graphite component 1.

[0042] In some embodiments of the present invention, when the raw material is petroleum coke, the petroleum coke needs to be heat treated before spheroidization.

[0043] In some embodiments of the present invention, the heat treatment temperature is 400-700°C, further 450-650°C.

[0044] In some embodiments of the present invention, the heat treatment time is 1-2 hours, further 1.5-1.8 hours.

[0045] In some embodiments of the present invention, the temperature of the graphitization treatment is 2800-3500°C, further 2900-3200°C.

[0046] In some embodiments of the present invention, the graphitization treatment time is 2-12 hours, further 3-10 hours.

[0047] In some embodiments of the present invention, the added amount of the asphalt is 1-5% by mass of the petroleum coke, and further 1.5-2.5%.

[0048] In some embodiments of the present invention, the granulation temperature is 700-800°C, further 750-780°C.

[0049] In some embodiments of the present invention, the granulation time is 30 minutes to 5 hours, further 1.5-4.5 hours. Granulation can obtain a graphite component with secondary particle structure characteristics.

[0050] In some embodiments of the present invention, the preparation process of the graphite component 1 includes: heat treating petroleum coke at a temperature of 400-700°C for 1-2 hours, then spheroidizing, and then graphitizing at a temperature of 2800-3500°C for 2-12 hours, adding asphalt, granulating at a temperature of 700-800°C for 30 minutes to 5 hours, to obtain the graphite component 1.

[0051] In some embodiments of the present invention, the raw material of the graphite component 2 includes needle coke, such as one of needle coke green coke and needle coke calcined coke.

[0052] In some embodiments of the present invention, the preparation process of the graphite component 2 includes: granulating needle coke, then graphitizing it, and then coating it to obtain the graphite component 2.

[0053] In some embodiments of the present invention, the coating treatment includes at least one of soft carbon liquid phase coating, hard carbon liquid phase coating, solid electrolyte coating, graphene coating or carbon nanotube coating.

[0054] In some embodiments of the present invention, the coating treatment adopts a conventional solid phase coating or liquid phase coating process.

[0055] In some embodiments of the present invention, during the coating process, at least one of asphalt, resin, biomass carbon source, solid electrolyte, graphene or carbon nanotubes may be added in an amount of 0.5-5.5% of the mass of the needle coke, further 0.5-5%.

[0056] In some embodiments of the present invention, the granulation and graphitization process in the preparation of the graphite component 2 is the same as the granulation and graphitization process of the graphite component 1.

[0057] In some embodiments of the present invention, the raw material of the graphite component 3 includes at least one of petroleum coke or needle coke, for example, one of petroleum coke green coke, petroleum coke calcined coke, needle coke green coke, and needle coke calcined coke.

[0058] In some embodiments of the present invention, the preparation process of the graphite component 3 includes: graphitizing petroleum coke or needle coke, then adding asphalt and conductive material to mix, and heating to obtain the graphite component 3.

[0059] In some embodiments of the present invention, when the raw material is petroleum coke green coke, the petroleum coke green coke needs to be heat treated before graphitization. When the raw material is petroleum coke calcined coke, needle coke green coke or needle coke calcined coke, no heat treatment is required.

[0060] In some embodiments of the present invention, the mass of the asphalt accounts for 0.1-6% of the mass of the petroleum coke or needle coke, and further 0.1-5%. Adding a small amount of asphalt helps the conductive material to evenly coat the petroleum coke or needle coke.

[0061] In some embodiments of the present invention, the mass of the conductive material accounts for 0.5-3%, further 0.5-2%, of the mass of the petroleum coke or needle coke.

[0062] In some embodiments of the present invention, the heating temperature after adding asphalt and conductive material to the mixture is 900-1300° C., and the heating time is 30 minutes to 5 hours.

[0063] In some embodiments of the present invention, the heat treatment and graphitization process in the preparation process of the graphite component 3 are the same as the heat treatment and graphitization process of the graphite component 1.

[0064] In some embodiments of the present invention, the raw material of the graphite component 4 includes petroleum coke, for example, at least one of petroleum coke green coke and petroleum coke calcined coke.

[0065] In some embodiments of the present invention, the preparation process of the graphite component 4 includes: spheroidizing petroleum coke and then graphitizing it to obtain the graphite component 4. The preparation process of the graphite component 4 does not involve granulation and coating.

[0066] In some embodiments of the present invention, when the raw material is petroleum coke, the petroleum coke needs to be heat treated before spheroidization.

[0067] In some embodiments of the present invention, the heat treatment and graphitization process in the preparation process of the graphite component 4 are the same as the heat treatment and graphitization process of the graphite component 1.

[0068] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: the present invention optimizes the interaction and influence of each graphite component by means of different designs for each graphite component; in graphite component 1, the kinetics and high-temperature performance are adjusted to a balanced state by means of spheroidization treatment; in graphite component 2, the stability of the graphite negative electrode is further improved by means of coating technology, by reducing the coating amount without damaging the kinetics; the surface of graphite component 3 is coated with a conductive coating layer that improves the compaction density and reduces the charge transfer impedance, which provides a basis for the use of the graphite negative electrode under high compaction; graphite component 4 uses petroleum coke as raw material, which can not only improve the processing performance of the graphite negative electrode, but also significantly reduce the raw material cost of the graphite pole piece.

[0069] According to another aspect of the present invention, a graphite negative electrode sheet is provided, wherein the components of the graphite negative electrode sheet include the above-mentioned graphite negative electrode, a current collector and an additive.

[0070] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: the graphite negative electrode plate of the present invention has high specific capacity and compaction density, and further, has good cycle performance, and can well solve the problems of lithium plating and capacity recovery rate after high-temperature storage (for example, the capacity recovery rate after storage at 60°C and 84 days exceeds 89%, or even exceeds 90%).

[0071] In some embodiments of the present invention, the current collector comprises copper foil or aluminum foil, preferably copper foil.

[0072] According to a preferred embodiment of the present invention, the graphite negative electrode sheet has at least the following beneficial effects: the compaction density of the graphite negative electrode sheet of the present invention is not less than 1.74 g / cc, and further exceeds 1.80 g / cc.

[0073] In some embodiments of the present invention, the auxiliary agent includes at least one of a conductive agent, a binder and a dispersant.

[0074] In some embodiments of the present invention, the auxiliary agent includes a conductive agent, a binder and a dispersant at the same time. In the graphite negative electrode sheet, the mass ratio of the graphite negative electrode, the conductive agent, the binder and the dispersant is 96: (1-4): (0.5-2): (0.5-2), and further is 96: (2-2.5): (0.8-1.2): (0.5-1.2).

[0075] In some embodiments of the present invention, the conductive agent can be a conventional conductive agent, such as conductive carbon black SP, acetylene black, Ketjen black, conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes.

[0076] Conductive agents are used to ensure that the electrodes have good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode sheet. It collects microcurrents between active materials and between active materials and current collectors (such as copper foil) to reduce the contact resistance of the electrodes and accelerate the movement rate of electrons. It can also effectively increase the migration rate of lithium ions in the electrode materials, thereby improving the charge and discharge efficiency of the electrodes. Conductive agents conventional in the art can be selected and added in conventional amounts without any restrictive provisions.

[0077] In some embodiments of the present invention, the binder may be a conventional binder, preferably a fluorine-based polymer and / or a synthetic rubber, more preferably one or a combination of at least two of polyvinyl fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, styrene butadiene rubber (SBR), fluorine-based rubber or ethylene propylene diene rubber.

[0078] The binder includes: a combination of polyvinyl fluoride and polyvinylidene fluoride, a combination of polytetrafluoroethylene and styrene-butadiene rubber type rubber, a combination of styrene-butadiene rubber, fluorine-based rubber and ethylene propylene diene rubber, a combination of polytetrafluoroethylene, styrene-butadiene rubber type rubber and fluorine-based rubber, a combination of polyvinyl fluoride, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber, a combination of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, fluorine-based rubber and ethylene propylene diene rubber, etc., and styrene-butadiene rubber (SBR) is particularly preferred.

[0079] In some embodiments of the present invention, the dispersant may be a conventional dispersant, such as sodium carboxymethyl cellulose (CMC-Na).

[0080] In some embodiments of the present invention, the auxiliary agent also includes a solvent, such as deionized water.

[0081] In some embodiments of the present invention, the compaction density of the graphite negative electrode sheet exceeds 1.65 g / cc, for example, 1.7-1.8 g / cc. The ultimate compaction density of the graphite negative electrode sheet is, for example, 1.74-1.82 g / cc.

[0082] According to another aspect of the present invention, a method for preparing a graphite negative electrode sheet is provided, comprising the following steps:

[0083] The graphite negative electrode is mixed with an auxiliary agent, and the obtained mixture is coated on a current collector, dried, and pressed to obtain the graphite negative electrode sheet.

[0084] In some embodiments of the present invention, the coating amount on the current collector is 80-120 g / m 2 , further to 100-110g / m 2 .

[0085] In some embodiments of the present invention, the solid content of the mixture is 40-50%, further 43-50%.

[0086] In some embodiments of the present invention, after the pressing is completed, a cutting operation is further included, and the cutting can obtain a graphite negative electrode sheet of a specific size.

[0087] According to another aspect of the present invention, a secondary battery is provided, comprising the above-mentioned graphite negative electrode sheet.

[0088] A secondary battery according to a preferred embodiment of the present invention has at least the following beneficial effects: the secondary battery of the present invention has good cycle performance, and can also well solve the problems of lithium plating and capacity recovery rate after high-temperature storage (for example, the capacity recovery rate after storage at 60°C for 84 days exceeds 89%, or even exceeds 90%).

[0089] In some embodiments of the present invention, the secondary battery is a lithium ion battery.

[0090] In some embodiments of the present invention, the secondary battery further comprises a positive electrode sheet, the raw materials for preparing the positive electrode sheet include a positive electrode active material, and the positive electrode active material is a conventional positive electrode active material, such as lithium iron phosphate or nickel cobalt manganese positive electrode active materials.

[0091] In some embodiments of the present invention, the raw materials for preparing the positive electrode sheet further include a conductive agent and a binder, which are conventional conductive agents and binders in the art.

[0092] In some embodiments of the present invention, the secondary battery further comprises an electrolyte, and the electrolyte comprises a lithium salt.

[0093] In some embodiments of the present invention, the lithium salt is preferably at least one of LiPF6, LiBF4, and LiTFSI. It can be any conventional lithium salt without any particular limitation.

[0094] In some embodiments of the present invention, the solvent of the electrolyte includes propylene carbonate, ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, N,N-dimethylacetamide, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfone, dimethyl ether, vinyl sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite or crown ether (12-crown-4) One or more.

[0095] In some embodiments of the present invention, the solvent is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0096] In some embodiments of the present invention, the volume ratio of EC, DEC and EMC in the solvent is (32-46): (25-36): 30.

[0097] In some embodiments of the present invention, the electrolyte further contains an additive; the mass fraction of the additive in the electrolyte is 0.1-18%, preferably 6-12%. Typical but non-limiting mass fractions of the additive in the electrolyte are 0.5%, 1.5%, 2.5%, 3.5%, 4.5%, 5.5%, 6.5%, 7.5%, 8.5%, 9.5%, 10.5%, 12%.

[0098] It is to be understood that the electrolyte additive is not particularly limited, and conventional electrolyte additives may be used.

[0099] Adding one or more additives to the electrolyte can further improve one or more properties of the secondary battery. According to the classification of the functions of the additives, the additives include film-forming additives (such as carbon dioxide, sulfur dioxide, lithium carbonate, carbonates, thioorganic solvents, halogenated organic film-forming additives, etc.), overcharge protection additives (having redox pairs: ortho- and para-dimethoxy-substituted benzene, polymerization increases internal resistance, blocks charging, such as biphenyl, cyclohexylbenzene, etc.), stabilizers, additives for improving high and low temperature performance, conductive additives or flame retardant additives (organic phosphides, organic fluorinated compounds, halogenated alkyl phosphates), etc.

[0100] In some embodiments of the present invention, the additives include fluoroethylene carbonate (FEC), vinylene carbonate (VC), cyclohexylbenzene (CHB), vinyl ethylene carbonate, 1,3-propane sultone (PS), 1,4-butane sultone, vinyl sulfate, propylene sulfate, ethylene sulfate, vinyl sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite, ethylene sulfite, methyl chloroformate, succinic anhydride (SA), dimethyl sulfoxide, anisole, acetamide, diazepine, diazepine One or more of benzene, 12-crown-4, 18-crown-6, 4-fluoroanisole, fluorinated chain ether, difluoromethylethylene carbonate, trifluoromethylethylene carbonate, chloroethylene carbonate, bromoethylene carbonate, trifluoroethylphosphonic acid, bromobutyrolactone, fluoroacetoxyethane, phosphate, phosphite, phosphazene, ethanolamine, carbodimethylamine, cyclobutyl sulfone, 1,3-dioxolane, acetonitrile, long-chain olefins, aluminum oxide, magnesium oxide, barium oxide, potassium carbonate, calcium carbonate, carbon dioxide, sulfur dioxide or lithium carbonate.

[0101] As the additive, one of the above-mentioned additives may be used alone or in combination of two or more.

[0102] In some embodiments of the present invention, vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC) and cyclohexylbenzene (CHB) are added to the electrolyte.

[0103] In some embodiments of the present invention, the secondary battery further comprises a separator. The separator is not particularly limited and can be a common separator in the art, such as a polyethylene (PE) separator, a polypropylene (PP) separator or a PE / PP composite separator.

[0104] According to another aspect of the present invention, an electric device is provided, comprising the above-mentioned secondary battery.

[0105] According to a preferred embodiment of the present invention, the electrical device has at least the following beneficial effects: the secondary battery of the present invention has a higher energy density and can support higher energy output. At the same time, it can maintain good working performance even in a high temperature environment and meet the use requirements of electronic devices such as electric vehicles and smart phones; the secondary battery of the present invention has good thermal stability and chemical stability, which reduces the occurrence of safety accidents in the electrical device during the power consumption process.

[0106] In some embodiments of the present invention, the power-consuming device is an electric vehicle, or other power-consuming devices such as energy storage systems, electric tools, drones, mobile devices such as wearable products, laptops, mobile phones, etc.

[0107] In some embodiments of the present invention, the power-consuming device is an electric car or an electric bicycle, or other electric vehicles, such as an electric motorcycle, an electric scooter, an electric wheelchair, etc.

[0108] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0109] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0110] Figure 1 It is a schematic diagram of the structure of the graphite component dispersion on one side of the current collector in the graphite negative electrode sheet of Example 1 of the present invention;

[0111] Figure 2 This is a scanning electron microscope image (SEM) of the graphite negative electrode sheet of Example 1 of the present invention.

[0112] Explanation of reference numerals: 1 represents graphite component 1; 2 represents graphite component 2; 3 represents graphite component 3, 4 represents graphite component 4; 5 represents current collector. DETAILED DESCRIPTION

[0113] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0114] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. "Between a and b" includes the endpoint values ​​of a and b.

[0115] Example 1

[0116] A graphite negative electrode comprises an active material, wherein the active material comprises a graphite component 1, a graphite component 2, a graphite component 3, and a graphite component 4;

[0117] The graphite component 1 accounts for 15% of the active material mass;

[0118] The graphite component 2 accounts for 50% of the active material mass;

[0119] The graphite component 3 accounts for 20% of the mass of the active material;

[0120] The graphite component 4 accounts for 15% of the mass of the active material;

[0121] Particle size D of graphite component 1 50 13.4μm;

[0122] Particle size D of graphite component 2 50 14.3μm;

[0123] Particle size D of graphite component 3 50 10.7μm;

[0124] Particle size D of graphite component 4 50 9.8μm;

[0125] The graphite component 1 has a secondary particle structure, the graphite component 1 is a secondary particle that has been spheroidized, the graphite component 1 contains a coating layer, the coating layer is composed of soft carbon, and the mass of the coating layer is 1.5% of the mass of the graphite component 1;

[0126] The graphite component 2 has a secondary particle structure, and the graphite component 2 contains a coating layer, the coating layer is composed of hard carbon, and the mass of the coating layer is 0.5% of the mass of the graphite component 2;

[0127] Both graphite component 3 and graphite component 4 have a single particle structure, and graphite component 3 contains a coating layer, the coating layer comprises graphene, and the mass of the graphene is 1% of the mass of graphite component 3, and graphite component 4 does not contain a coating layer.

[0128] The method for preparing the above graphite negative electrode comprises the following steps:

[0129] Mixing the graphite components to obtain a graphite negative electrode;

[0130] The preparation process of graphite component 1 includes: heat treating petroleum coke at a temperature of 500° C. for 1 hour, then spheroidizing (spheroidizing is a conventional process in the art), then graphitizing at a temperature of 3000° C. for 3 hours, adding asphalt (the mass of asphalt is 7.5% of the mass of petroleum coke), granulating at a temperature of 750° C. for 2 hours, and obtaining graphite component 1;

[0131] The preparation process of the graphite component 2 includes: granulating the needle coke at a temperature of 750° C. for 2 hours, then graphitizing the needle coke at a temperature of 3000° C. for 3 hours, adding a polycarbonate resin (the mass of the polycarbonate resin is 5% of the mass of the needle coke), and coating the needle coke using a conventional liquid phase coating process to obtain the graphite component 2;

[0132] The preparation process of graphite component 3 includes: graphitizing petroleum coke calcined coke, the graphitization temperature is 3000°C, the graphitization time is 3 hours, and then adding asphalt (the mass of asphalt is 5% of the mass of petroleum coke calcined coke, and the asphalt softening point temperature is 300°C), conductive material (the conductive material is graphene, and the mass of graphene is 1.0% of the mass of petroleum coke calcined coke), heating to 350°C, stirring and mixing, heating, the heating temperature is 1000°C, and the heating time is 2 hours, to obtain graphite component 3.

[0133] The preparation process of graphite component 4 includes: heat treating petroleum coke at a temperature of 550° C. for 1.5 hours, then spheroidizing, and then graphitizing at a temperature of 3200° C. for 1.5 hours to obtain graphite component 4. The preparation process of graphite component 4 does not involve granulation and coating.

[0134] A graphite negative electrode sheet comprises a graphite negative electrode, a current collector (the current collector is a copper foil), a conductive agent, a binder and a dispersant.

[0135] In the graphite negative electrode sheet, the mass ratio of the graphite negative electrode, the conductive agent, the binder and the dispersant is 96:2:1:1.

[0136] The conductive agent is conductive carbon black SP; the binder is styrene-butadiene rubber (SBR); and the dispersant is sodium carboxymethyl cellulose (CMC-Na).

[0137] The compaction density of the graphite negative electrode sheet is 1.70 g / cc. During the rolling process, the ultimate compaction density of the graphite negative electrode sheet is verified by adjusting the roller press parameters.

[0138] A method for preparing a graphite negative electrode sheet comprises the following steps:

[0139] The graphite negative electrode is mixed with a conductive agent, a binder and a dispersant, and deionized water, and the obtained mixture (the solid content of the mixture is 45%) is coated at a coating amount of 100 g / m 2 The graphite negative electrode sheet is obtained by coating the upper and lower surfaces of the copper foil, drying, and rolling twice.

[0140] Figure 1 Schematic diagram of the structure of the graphite components dispersed on one side of the current collector in the graphite negative electrode sheet of Example 1 of the present invention; Figure 1 It can be seen that the four graphite components in the active material are dispersed with each other.

[0141] Figure 2 This is a scanning electron microscope image (SEM) of the graphite negative electrode sheet of Example 1 of the present invention.

[0142] The above-mentioned graphite negative electrode sheet and lithium sheet are assembled into a half-cell, and the assembled half-cell is used to test the gram capacity of the active material.

[0143] The above-mentioned graphite negative electrode sheet is assembled with PP (polypropylene) separator, electrolyte (0.1 mol / L LiPF6 EC as solvent), and lithium iron phosphate positive electrode to form a soft-pack full battery. The full-battery soft pack is used to test the first coulomb efficiency (first efficiency) of the battery cell, the capacity retention rate of 500 charge and discharge cycles in the 2C stage, the lithium plating degree of 50 charge and discharge cycles in the 3C stage, and the capacity recovery rate after storage at 60°C for 84 days.

[0144] Examples 2-18 and Comparative Examples 1-11

[0145] The preparation process of the graphite negative electrode corresponding to Examples 2-18 and Comparative Examples 1-16 is similar to that of Example 1, except that the content of each graphite component in the active material is different, the particle size of each graphite component is different, and the composition of the coating layer or the mass proportion of the coating layer is different. The specific situation is shown in Table 1 (for the convenience of comparison, Table 1 also lists the composition characteristics of the active material corresponding to Example 1. The characteristics of Examples 2-18 and Comparative Examples 1-16 not listed in Table 1 are the same as those of Example 1).

[0146] The testing process of the gram capacity of the active material is as follows: the half-cell is tested at 0.1C, the charge cut-off voltage is 2V, and the discharge cut-off voltage is 0.05V to obtain the gram capacity of the active material.

[0147] The ultimate compaction density of graphite negative electrode plate: It is verified by adjusting the roller pressure of the roller machine, and whether there is over-pressure is judged by whether there is a bulge on the surface of the electrode plate. The electrode plate compaction density corresponding to no over-pressure is the ultimate compaction density of the graphite negative electrode plate.

[0148] The first coulombic efficiency (first efficiency) of the battery cell is tested under the conditions of a charging cut-off voltage of 3.75V and a discharging cut-off voltage of 2V, and the charging process is divided into two steps. The first step is to charge to 50% SOC with a current of 0.05C, and then charge to 100% SOC with a current of 0.33C (100% SOC means fully charged), and the discharge current is 0.33C.

[0149] The capacity retention rate after 500 charge and discharge cycles in the 2C stage and the lithium plating degree after 50 charge and discharge cycles in the 3C stage are both tested under the conditions of a charge cut-off voltage of 3.75V and a discharge cut-off voltage of 2V.

[0150] The test process of the capacity recovery rate after storage at 60℃ for 84 days is as follows: the battery is charged to a voltage of 3.75V at a current of 0.33C at 25℃, the battery is stored in a 60℃ environment for 84 days, then discharged to 2V at a current of 0.33C, then charged to 3.75V at 0.33C and discharged to 2V at 0.33C to obtain the recovery capacity C1. C1 divided by the initial capacity (the initial capacity is the capacity corresponding to the capacity before high-temperature storage) is the capacity recovery rate after storage at 60℃ for 84 days.

[0151] When the coating components of graphite component 1 and graphite component 2 in Table 1 are soft carbon, the raw material corresponding to the soft carbon is conventional asphalt. When the coating component of graphite component 2 is hard carbon, the raw material corresponding to the hard carbon is biomass raw material (such as corn stalk powder).

[0152] Table 1 (0% in Table 1 means no corresponding graphite component)

[0153]

[0154]

[0155]

[0156] The gram capacity of active materials, the ultimate compaction density of graphite negative electrode sheets, the first efficiency of the battery cell, the capacity retention rate of 500 charge and discharge cycles in the 2C stage, the degree of lithium plating after 50 charge and discharge cycles in the 3C stage, and the capacity recovery rate after storage at 60°C for 84 days corresponding to the above-mentioned Examples 1-18 and Comparative Examples 1-11 are shown in Table 2.

[0157] Table 2

[0158]

[0159]

[0160]

[0161] The active material in the multi-component graphite negative electrode plate proposed in the present invention is composed of different graphite components, each of which has different functions and effects. The graphite component 1 is selected from petroleum coke raw coke or petroleum coke calcined coke as raw material, and is subjected to spheroidization, graphitization, and granulation to form graphite with a secondary particle structure. The purpose of introducing the graphite component 1 is to take into account both high-temperature performance and dynamic performance, and to utilize the advantages of the raw materials and the secondary particle structure to improve the intrinsic dynamic performance of the graphite material as much as possible. The high-activity sites of the side reactions such as the end faces and edges of the graphite particles are removed by spheroidization to ensure high-temperature performance. In Example 1, Example 2, Comparative Example 1, and Comparative Example 5, the proportion of graphite component 1 was adjusted for verification. In Example 2, as the proportion of graphite component 1 decreased, the dynamic performance decreased significantly, and the capacity retention rate of 500 charge and discharge cycles in the 2C stage was lower than that in Example 1, and was accompanied by a slight degree of lithium precipitation. In addition, since the content of the graphite component is changed in Comparative Examples 1 and 5, the dynamics of the graphite component 1 itself cannot be highlighted. Therefore, in Comparative Examples 1 and 5, the corresponding capacity, compaction density, cycle retention rate and lithium precipitation are all poor.

[0162] The graphite component 2 uses needle coke raw coke or needle coke calcined coke as raw material and liquid phase coating to obtain secondary particle graphite with low residual carbon content (i.e., low coating layer content). The purpose is to improve the compaction density and capacity of the graphite negative electrode plate with the unique streamline of the raw material, and to reduce the residual carbon content and ensure the dynamic performance at the 3C level by using the coating technology. The content of the graphite component 2 was adjusted in Example 1, Example 4, Example 5, Comparative Example 2, and Comparative Example 6 for verification. Compared with Example 1, the proportion of the graphite component 2 was increased and decreased in Example 4 and Example 5, respectively. It can be found that the dynamic performance is improved as the proportion of the graphite component 2 increases. When the proportion of the graphite component 2 reaches 50%, the dynamic requirements of the 3C level can be met. Further increasing the proportion of the graphite component 2 on this basis does not improve the dynamics much, and it is easy to cause the high temperature performance to deteriorate, resulting in unsatisfactory high temperature storage performance. In Comparative Examples 2 and Comparative Examples 6, the problem of deterioration of high temperature performance is further manifested, and affected by the graphite component 2 of the secondary particle structure, the capacity and first effect in Comparative Examples 2 and Comparative Examples 6 are also much lower than that in Example 1.

[0163] Graphite component 3 uses petroleum coke calcined coke as raw material, and the surface is coated with graphene, carbon nanofibers, etc. to form large-particle graphite with a conductive coating layer that increases compaction density and reduces charge transfer resistance, the purpose of which is to increase the capacity and compaction density of the active material. The proportion of graphite component 3 was adjusted in Example 1, Example 5, Example 10, Comparative Example 3, and Comparative Example 7. The proportion of graphite component 3 in Example 5 and Example 10 increased and decreased respectively compared with Example 1. As the proportion of graphite component 3 increased, the capacity and compaction density were improved, but limited by insufficient kinetic performance, the cycle retention rate and lithium precipitation were poor. When the proportion of graphite component 3 was low, the active material capacity and compaction density became limiting points; Comparative Examples 3 and Comparative Examples 7 further highlight the characteristics of graphite component 3 with insufficient kinetic performance but high capacity and compaction density.

[0164] Graphite component 4 uses petroleum coke as raw material to obtain single-grain structure graphite, which reduces costs on the one hand and makes up for the problem of insufficient dynamic performance of single-grain structure graphite on the other hand. The high-temperature performance of petroleum coke is poor by spheroidizing. By comparing Example 1, Example 3, Comparative Example 4, and Comparative Example 8, it can be found that as the proportion of graphite component 4 decreases, the capacity and high-temperature performance of the active material tend to deteriorate. Similar to graphite component 3, as the proportion is too high, the fast charging performance deteriorates and becomes a limiting point.

[0165] In the process of adjusting the proportion of each graphite component, it can be found (Example 1, Examples 6-10) that the capacity and compaction density of the active substance can be regulated by increasing or decreasing the proportion of one of the graphite components. Graphite component 1 and graphite component 2 can be roughly regarded as switches for adjusting the kinetic properties, and graphite component 3 and graphite component 4 can be regarded as switches for capacity and compaction density.

[0166] In addition, in Examples 11-18 and Comparative Examples 9-11, by adjusting the particle size of each graphite component and the composition of the coating layer, it can be found that the particle size of each graphite component has an important influence on the capacity, compaction density and first effect of the battery cell. This is because the change in the particle size of the graphite particles will lead to changes in the structure of the particle part on the surface of the pole piece, resulting in an increase or decrease in the pore structure, thereby causing changes in the compaction density and first effect. At the same time, the particle size of the graphite particles themselves has a crucial influence on the kinetic performance, and the kinetic performance gradually weakens as the particle size increases; in Examples 13-15, the coating of the surface of each graphite component is changed by changing the composition of the coating layer, and satisfactory electrochemical performance is shown when the proportion and particle size are appropriate.

[0167] In summary, the present invention uses a variety of different graphite components in combination, and coordinates the particle size of the graphite components and the proportion of the graphite components in the active material, so that the graphite negative electrode and the graphite negative electrode plate obtained by the present invention have good electrical properties.

[0168] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A graphite negative electrode, characterized in that: The active material comprises at least two of graphite component 1, graphite component 2, graphite component 3, and graphite component 4, and does not comprise only graphite component 1 and graphite component 4 at the same time; The graphite component 1 and the graphite component 2 both have a secondary particle structure, and the graphite component 1 is a secondary particle that has been spheroidized, and the graphite component 2 contains a coating layer; The graphite component 3 and the graphite component 4 both have a single particle structure, and the graphite component 3 contains a coating layer, while the graphite component 4 does not contain a coating layer.

2. The graphite negative electrode according to claim 1, characterized in that The graphite component 1 accounts for 0-30% of the mass of the active material; and / or, the graphite component 2 accounts for 0-70% of the mass of the active material; and / or, the graphite component 3 accounts for 0-70% of the mass of the active material; and / or, the graphite component 4 accounts for 0-30% of the mass of the active material; and / or, the particle size D of the graphite component 1 50 Between 11.5-14 μm; and / or, the particle size D of the graphite component 2 50 Between 13-15 μm; and / or, the particle size D of the graphite component 3 50 Between 9-13 μm; and / or, the particle size D of the graphite component 4 50 Between 8-11μm.

3. The graphite negative electrode according to claim 1, characterized in that The active material comprises graphite component 2, graphite component 3 and graphite component 4; and / or, the graphite component 2 accounts for 15-60% of the mass of the active material; And / or, the particle size D of the graphite component 2 50 Between 13-14.5 μm; and / or, the graphite component 3 accounts for 10-60% of the mass of the active material; And / or, the particle size D of the graphite component 3 50 Between 9.5-12.5 μm; and / or, the graphite component 4 accounts for 10-30% of the mass of the active material; And / or, the particle size D of the graphite component 4 50 Between 9-11μm.

4. The graphite negative electrode according to claim 1, characterized in that The graphite component 1 accounts for 10-25% of the mass of the active material; And / or, the particle size D of the graphite component 1 50 Between 12-14 μm; And / or, the graphite component 1 contains a coating layer, and the coating layer accounts for 1.2-2% of the mass of the graphite component 1; and / or, the coating layer in the graphite component 2 accounts for 0.2-1.5% of the mass of the graphite component 2; And / or, the coating layer of the graphite component 3 is a conductive coating layer.

5. The method for preparing a graphite negative electrode according to any one of claims 1 to 4, characterized in that: The steps include: The various graphite components are mixed to obtain the graphite negative electrode.

6. The preparation method according to claim 5, characterized in that: The raw material of the graphite component 1 includes petroleum coke; and / or, the raw material of the graphite component 2 includes needle coke; And / or, the raw material of the graphite component 3 includes at least one of petroleum coke or needle coke; And / or, the raw material of the graphite component 4 includes petroleum coke.

7. The preparation method according to claim 6, characterized in that: The preparation process of the graphite component 1 includes: spheroidizing petroleum coke, graphitizing it, adding asphalt, and granulating it to obtain the graphite component 1; And / or, the preparation process of the graphite component 2 includes: granulating needle coke, then graphitizing it, and then coating it to obtain the graphite component 2; the coating treatment is at least one of soft carbon liquid phase coating, hard carbon liquid phase coating, solid electrolyte coating, graphene coating, and carbon nanotube coating after graphitization; And / or, the preparation process of the graphite component 3 includes: graphitizing petroleum coke or needle coke, then adding asphalt and conductive material to mix, and heating to obtain the graphite component 3; And / or, the preparation process of the graphite component 4 includes: spheroidizing petroleum coke and then graphitizing it to obtain the graphite component 4.

8. A graphite negative electrode plate, characterized in that: The components of the graphite negative electrode sheet include the graphite negative electrode according to any one of claims 1 to 4, a current collector and an additive.

9. A secondary battery, characterized in that: Comprising the graphite negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Negative plate, preparation method thereof and battery

    CN116190562A

  • Preparation method of high-compaction-density composite negative electrode graphite material

    CN113422024A

  • Graphite particle, lithium ion secondary battery and negative electrode material thereof

    JP2009227579A

  • Composite graphite material, method for preparing same, negative electrode sheet, secondary battery, battery module, battery pack, and electrical apparatus

    US20230416097A1

  • Secondary battery, electric device and preparation method

    WO2024082273A1

Cited By

  • Graphite negative electrode, preparation method therefor, and use thereof

    WO2026103186A1